Towards the suitable monitoring of ingestion of microplastics by marine biota: A review. (November 2016) - Wesch, Charlotte; Bredimus, Katja; Paulus, Martin; Klein, Roland
Abstract: Monitoring plastic ingestion in marine biota is a difficult task, especially regarding ubiquitous microplastics (particles of <5 mm). Due to their microscopic size, evidence for microplastic ingestion is often limited to laboratory studies. The following review provides a comparison and assessment of different microplastic ingestion monitoring procedures. Emphasis is given to the most important steps of current monitoring practice: (1) selecting suitable indicator species, (2) sampling and sample processing, (3) analytical procedures and (4) the prevention of secondary contamination of the sample. Moreover, an overview on ingestion records of microplastics by different marine feeding guilds is presented, including filter, suspension and deposit feeders as well as predators and scavengers. Lastly, monitoring processes are addressed critically in terms of their suitability for achieving the aims of an appropriate monitoring programme. Recommendations for future research priorities are presented with a focus on the necessity of standardised and comparable monitoring procedures in microplastic detection. Highlights: Comparison and assessment of different microplastic ingestion monitoring procedures. Overview on ingestion records of microplastics by different marine feeding guilds. Necessity of standardised and comparable monitoring procedures in microplastic detection. Recommendations for future research priorities in microplastic ingestion monitoring. Abstract : Monitoring procedures and recommendations for future research are presented emphasizing the necessity for standardised measures for microplastic detection.